A Post-segregational Killing Mechanism for Maintaining Plasmid PMF1 in Its Myxococcus fulvus Host - Li, Ya-jie; Liu, Ya; Zhang, Zheng; Chen, Xiao-jing; Gong, Ya; Li, Yue-zhong (Frontiers in Cellular and Infection Microbiology, 2018)
Although plasmids provide additional functions for cellular adaptation to the environment, they also create a metabolic burden, which causes the host cells to be less competitive with their siblings. Low-copy-number plasmids have thus evolved several mechanisms for their long-term maintenance in host cells. pMF1, discovered in Myxococcus fulvus 124B02, is the only endogenous autonomously replicated plasmid yet found in myxobacteria. Here we report that a post-segregational killing system, encoded by a co-transcriptional gene pair of pMF1.19 and pMF1.20, is involved in maintaining the pMF1 plasmid in its host cells. We demonstrate that the protein encoded by pMF1.20 is a new kind of nuclease, which is able to cleave DNA in vitro. The nuclease activity can be neutralized by the protein encoded by pMF1.19 through protein–protein interaction, suggesting that the protein is an immune protein for nuclease cleavage. We propose that the post-segregational killing mechanism of the nuclease toxin and immune protein pair encoded by pMF1.20 and pMF1.19 is helpful for the stable maintenance of pMF1 in M. fulvus cells.